Pengaruh Daya Tarik Iklan, Brand Image, dan Emotional Branding Terhadap Loyalitas Konsumen (Studi Pada Followers Akun Instagram @rucas.co) - Kharisma Agustia Intan Permatasari1; Novita Haryono (Jurnal Komunikasi Massa, 2026)
The rapid advancement of social media in Indonesia has brought new opportunities for marketing communication, while also demanding different strategies to ensure messages are delivered effectively. As a platform with over 100 million active users, Instagram has become a potential medium for building consumer loyalty in the digital era. RUCAS.CO, as a local fashion brand, utilizes a unique differentiation strategy by featuring non-conventional talents such as scavengers, parking attendants, street musicians, and even punks, to build advertising appeal, brand image, and emotional branding. The uniqueness of this strategy, which has never been studied in local fashion brands, prompted the researcher to analyze the influence of these three variables on consumer loyalty among followers of the @rucas.co Instagram account. This research employs the Stimulus-Organism-Response (S-O-R) theoretical framework proposed by Carl Hovland to explain how advertising appeal, brand image, and emotional branding function as stimuli that influence consumer perceptions before generating a loyalty response. The study uses a quantitative approach, with multiple linear regression analysis conducted on 100 respondents selected through purposive sampling—those who have followed the account for at least three months and have purchased a product. Data was collected through an online questionnaire using a 1–5 Likert scale, and tested for validity and reliability with SPSS software. The findings indicate that advertising appeal, brand image, and emotional branding each significantly influence consumer loyalty. Simultaneously, these three variables have a significant effect and are able to explain 59.1% of the variation in consumer loyalty. Brand image has the highest coefficient (0.412), followed by advertising appeal (0.329), and emotional branding (0.281). These results affirm that a combination of attractive advertisements, a strong brand image, and emotional bonds effectively build customer loyalty through social media.